Optomechanical assessment of photorefractive corneal cross-linking via optical coherence elastography - Frigelli, Matteo; Büchler, Philippe; Kling, Sabine (Frontiers in Bioengineering and Biotechnology, 2023)
Corneal cross-linking (CXL) has recently been used with promising results to positively affect corneal refractive power in the treatment of hyperopia and mild myopia. However, understanding and predicting the optomechanical changes induced by this procedure are challenging.Methods: We applied ambient pressure modulation based optical coherence elastography (OCE) to quantify the refractive and mechanical effects of patterned CXL and their relationship to energy delivered during the treatment on porcine corneas. Three different patterned treatments were performed, designed according to Zernike polynomial functions (circle, astigmatism, coma). In addition, three different irradiation protocols were analyzed: standard Dresden CXL (fluence of 5.4 J/cm 2 ), accelerated CXL (fluence of 5.4 J/cm 2 ), and high-fluence CXL (fluence of 16.2 J/cm 2 ). The axial strain distribution in the stroma induced by ocular inflation (Δp=30 mmHg) was quantified, maps of the anterior sagittal curvature were constructed and cylindrical refraction was assessed.Results: Thirty minutes after CXL, there was a statistically significant increase in axial strain amplitude (p<0.050) and a reduction in sagittal curvature (p<0.050) in the regions treated with all irradiation patterns compared to the non-irradiated ones. Thirty-six hours later, the non-irradiated regions showed compressive strains, while the axial strain in the CXL-treated regions was close to zero, and the reduction in sagittal curvature observed thirty minutes after the treatment was maintained. The Dresden CXL and accelerated CXL produced comparable amounts of stiffening and refractive changes (p=0.856), while high-fluence CXL produced the strongest response in terms of axial strain (6.9 ± 1.9‰) and refractive correction (3.4 ± 0.9 D). Tripling the energy administered during CXL resulted in a 2.4-fold increase in the resulting refractive correction.Conclusions: OCE showed that refractive changes and alterations in corneal biomechanics are directly related. A patient-specific selection of both, the administered UV fluence and the irradiation pattern during CXL is promising to allow customized photorefractive corrections in the future.